2010
DOI: 10.1093/jac/dkq455
|View full text |Cite
|
Sign up to set email alerts
|

Host range of enterococcal vanA plasmids among Gram-positive intestinal bacteria

Abstract: Intra-species transfer of enterococcal vanA plasmids was far more frequent than transfer across species or genus barriers and may thus explain the preferred prevalence of vanA-containing plasmids among E. faecium. A reservoir of vanA plasmids in non-enterococcal intestinal colonizers does not seem to be reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 69 publications
1
52
0
Order By: Relevance
“…and Bifidobacterium spp. ), no transfer of vanA between genera was observed (36). Interestingly, the authors observed that interspecies transmission within the Enterococcus genus, e.g., E. faecium to E. faecalis, occurred at a much lower frequency (1/10 8 per donor/ recipient) than intraspecies transmission (1/10 6 per donor/recipient).…”
Section: Antimicrobial Resistance Mechanisms and Approaches To Therapymentioning
confidence: 97%
“…and Bifidobacterium spp. ), no transfer of vanA between genera was observed (36). Interestingly, the authors observed that interspecies transmission within the Enterococcus genus, e.g., E. faecium to E. faecalis, occurred at a much lower frequency (1/10 8 per donor/ recipient) than intraspecies transmission (1/10 6 per donor/recipient).…”
Section: Antimicrobial Resistance Mechanisms and Approaches To Therapymentioning
confidence: 97%
“…Exchange of resistant strains among different ecosystems is less probable due to the supposed ecovar association, especially among hospital-associated E. faecium strains (see chapter 5), although dissemination across host barriers of vancomycin-and multi-resistant enterococci was described anecdotally, especially for the less strongly host-adapted E. faecalis strains (Manson et al, 2003a;Manson et al, 2003b;Manson et al, 2004;Agerso et al, 2008;Larsen et al, 2010;Hammerum et al, 2010;Freitas et al, 2011a). Vancomycin resistance among enterococci most probably spreads via a dissemination of mobile genetic elements of variants of the vanA-type element Tn1546 mostly located on mobilizable or conjugative plasmids (Sletvold et al, 2007;Novais et al, 2008;Sletvold et al, 2008;Freitas et al, 2009;Rosvoll et al, 2009;Sletvold et al, 2010;Laverde Gomez et al, 2011;Werner et al, 2011b;Freitas et al, 2011b). In vitro transfer of vanA plasmids has been determined in a number of studies (Werner et al, 1997;van den Braak et al, 1998;Werner et al, 2010b) and transfer in vivo in digestive tracts of animals and human volunteers was also shown (Moubareck et al, 2003;Lester et al, 2006;Lester and Hammerum 2010).…”
Section: Localization and Spread Of Vana-and Vanb-type Resistancementioning
confidence: 99%
“…Transferability of Tn5801 was screened by filter mating using different recipient strains of E. faecalis (JH2-2, OG1RF, and OG1SSp) and E. faecium (64/3, BM4105RF, and BM4105SS), all being resistant to rifampin and fusidic acid (designated RF) or streptomycin and spectinomycin (designated SS) and negative for the presence of the tet(M) gene (32). The mating assays were performed at 37°C for 36 h using aliquots of broth cultures of donors and recipients grown up to the exponential phase (McFarland 0.5) and mixed at a ratio of 1:1 (32).…”
Section: Screening Of Tn5801 In Genbank Databases and Creation Of Datmentioning
confidence: 99%
“…Transferability of Tn5801 was screened by filter mating using different recipient strains of E. faecalis (JH2-2, OG1RF, and OG1SSp) and E. faecium (64/3, BM4105RF, and BM4105SS), all being resistant to rifampin and fusidic acid (designated RF) or streptomycin and spectinomycin (designated SS) and negative for the presence of the tet(M) gene (32). The mating assays were performed at 37°C for 36 h using aliquots of broth cultures of donors and recipients grown up to the exponential phase (McFarland 0.5) and mixed at a ratio of 1:1 (32). Transconjugants were selected on brain heart infusion (BHI) agar (Pronadisa, Laboratorios Conda, SA, Madrid, Spain) plates supplemented with tetracycline (10 mg/liter) plus rifampin (30 mg/liter) and fusidic acid (25 mg/ liter) or streptomycin (250 mg/liter) and spectinomycin (250 mg/liter) (Sigma-Aldrich, Inc., St. Louis, MO).…”
Section: Screening Of Tn5801 In Genbank Databases and Creation Of Datmentioning
confidence: 99%